Adenosine A1 receptor inhibits postnatal neurogenesis and sustains astrogliogenesis from the subventricular zone. Issue 9 (15th June 2016) - Benito‐Muñoz, Monica; Matute, Carlos; Cavaliere, Fabio
Abstract : We previously demonstrated that activation of ATP P2X receptors during oxygen and glucose deprivation inhibits neuroblast migration and in vitro neurogenesis from the subventricular zone (SVZ). Here, we have studied the effects of adenosine, the natural end‐product of ATP hydrolysis, in modulating neurogenesis and gliogenesis from the SVZ. We provide immunochemical, molecular and pharmacological evidence that adenosine via A1 receptors reduces neuronal differentiation of neurosphere cultures generated from postnatal SVZ. Furthermore, activation of A1 receptors induces downregulation of genes related to neurogenesis as demonstrated by gene expression analysis. Specifically, we found that A1 receptors trigger a signaling cascade that, through the release of IL10, turns on the Bmp2/SMAD pathway. Furthermore, activating A1 receptors in SVZ‐neural progenitor cells inhibits neurogenesis and stimulates astrogliogenesis as assayed in vitro in neurosphere cultures and in vivo in the olfactory bulb. Together, these data indicate that adenosine acting at A1 receptors negatively regulates adult neurogenesis while promoting astrogliogenesis, and that this feature may be relevant to pathological conditions whereby purines are profusely released. GLIA 2016;64:1465–1478 Main points: Adenosine reduces post‐natal rat neurogenesis via activation of A1 receptors. Activation of A1 receptors triggers the release of IL10 and activation of STAT3/Bmp2 pathway. This cascade of events leads to the activation of astrogliogenesis.